Smart biosecurity door locking system / Nur Nadia Syahirah ‘Asri - ‘Asri, Nur Nadia Syahirah (2017)
Biometric technology which can be used to recognize an individual’s identity based on his or her behavioral or physiological characteristics has become one of the most publicized authentication method. Fingerprint authentication has been chosen among other biometric technologies such as hand geometry, keystroke, hand vein, face recognition, iris recognition, signature, voice recognition and gait due to its uniqueness. Besides that, fingerprint has high performance, high distinctive and only requires short processing time. This study uses biometric technology which is fingerprint authentication implemented for door locking system as people nowadays need security systems in every single aspects especially for home security. This system does not require the use of smart card or even password to remember. Furthermore, the system was developed using Fingerprint Matching Algorithm (FMA), Image Processing technique and embedded programming technique. Visual Studio has been used in order to code the program in C#. In addition, some research has been made through observation as well as referring to the published materials and the existing application of fingerprint and Raspberry Pi. In this paper, Rational Unified Process (RUP) is being used in order to accomplish a perfect result and ensure that the objectives of the project can be achieved. This methodology is chosen because it is suitable for small development teams. There are four phases involved which are inception, elaboration, construction and lastly, transition. As expected, the algorithm applied in this project is effective and can help users to increase their home security level. In conclusion, this project was a success and satisfied all scopes required.